Patterns of anxiety and distress over 12 months following participation in HPV primary screening. (3rd August 2021) - Marlow, Laura A V; McBride, Emily; Ridout, Deborah; Forster, Alice S; Kitchener, Henry; Waller, Jo
Abstract : Objectives: Many countries are now using primary human papillomavirus (HPV) testing for cervical screening, testing for high-risk HPV and using cytology as triage. An HPV-positive result can have an adverse psychological impact, at least in the short term. In this paper, we explore the psychological impact of primary HPV screening over 12 months. Methods: Women were surveyed soon after receiving their results (n=1133) and 6 (n=762) and 12 months (n=537) later. Primary outcomes were anxiety (Short-Form State Anxiety Inventory-6) and distress (General Health Questionnaire-12). Secondary outcomes included concern, worry about cervical cancer and reassurance. Mixed-effects regression models were used to explore differences at each time point and change over time across four groups according to their baseline result: control (HPV negative/HPV cleared/normal cytology and not tested for HPV); HPV positive with normal cytology; HPV positive with abnormal cytology; and HPV persistent (ie, second consecutive HPV-positive result). Results: Women who were HPV positive with abnormal cytology had the highest anxiety scores at baseline (mean=42.2, SD: 15.0), but this had declined by 12 months (mean=37.0, SD: 11.7) and was closer to being within the 'normal' range (scores between 34 and 36 are considered 'normal'). This group also had the highest distress at baseline (mean=3.3, SD: 3.8, scores of 3+ indicate case-level distress), but the lowest distress at 12 months (mean=1.9, SD: 3.1). At 6 and 12 months, there were no between-group differences in anxiety or distress for any HPV-positive result group when compared with the control group. The control group were less concerned and more reassured about their result at 6 and 12 months than the HPV-positive with normal cytology group. Conclusions: Our findings suggest the initial adverse impact of an HPV-positive screening result on anxiety and distress diminishes over time. Specific concerns about the result may be longer lasting and efforts should be made to address them.